Dissipation of Turbulent Kinetic Energy in a Cylinder Wall Junction Flow - Schanderl, Wolfgang; Manhart, Michael (Flow, turbulence and combustion, 2018)
The subject of this study is the discussion of the dissipation of turbulent kinetic energy and its Reynolds number scaling in front of a wall-mounted cylinder. We employed highly resolved Large-Eddy Simulation and ensured that the computational grid was fine enough to resolve most of the scales. A perceptible fraction of the total dissipation is modeled. However, this fraction - about one third - is small enough so that the total dissipation suffers only marginally from some potential shortcomings of the turbulence model. Individual terms of the pseudo dissipation tensor and their Reynolds number scaling are discussed and compared. This tensor and thus the turbulent small scale structures are not isotropic at the Reynolds numbers investigated. Furthermore, the near-wall anisotropy under the horseshoe vortex is likely to persist to larger Reynolds numbers as it can be linked to a flapping of the near-wall layer. The turbulent length scale shows a strong spatial variability. In the region of the vortex system in the cylinder front, the distribution reveals a similar shape as the one of the turbulent kinetic energy and its amplitude is in the order of magnitude of the cylinder diameter. In contrast to the region dominated by the approach flow, the turbulent length scale is independent of the Reynolds number in the region dominated by the vortex system. Even though the flow investigated is in non-equilibrium, common a priori estimations and scalings of the Kolmogorov length scale based on macro scales give satisfying results.